Cyberspace Missionaries: A Profile of Dynamic Digital Age Evangelism - Hia, Yeremia; Halawa, Jonius (TELEIOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
The development of digital technology has changed the way the gospel is spread, presenting new challenges and opportunities for missionaries. The digital age creates cyberspace as a vast and dynamic field of service, so a cyberspace missionary figure is needed who is able to combine the spirit of evangelism with digital skills. This research aims to identify the profile of cyber missionaries and the strategies used in spreading the gospel in the digital realm. The method used is qualitative with a case study approach, involving in-depth interviews and digital content analysis of several missionaries active on social media platforms. The results show that cyber missionaries rely not only on theological knowledge, but also digital technology and communication skills that are adaptive to new trends. The novelty of this research lies in the comprehensive mapping of digital missionary profiles as well as the emphasis on creativity and ethical aspects in digital ministry. The findings make an important contribution to the development of effective mission strategies in the ever-changing digital age. The implications of this study highlight the importance of training and capacity building for digital missionaries to be more effective in spreading the gospel in the technological age.